Effect of particle size on the extraction of oil and protein from fresh coconut meat (Part I-Laboratory) - Gonzales, Antonia L; Claudio, Teresita R.; Buccat, Eleonor F.; Mañalac, Guillermina (1982)
The effect of different size-reduction equipment of the extraction of oil and protein from coconut meat was investigated. Laboratory scale studies showed that meat passed through the colloid mil had the finest particle size and gave the highest amount of extracted oil and protein. Using a laboratory carves press, about 81.5% of the oil andf 74.66% of the protein in the meat may be extracted when the meat is reduced to colloidal size prior to pressing.